Otentisitas Komunikator dan Motivasi Menulis Mahasiswa di Media Sosial - Zainurrahman Zainurrahman (Kantor Bahasa Provinsi Maluku Utara, 2016)
This research is accomplished to understand the triggers of the university students’ motivation in writing through social medium networks which is suspected by writing-matrix project, it is wellknown as ‘communicator authenticity’ which provides an authentic textual interaction. It is realized that the frequency of students’ writing activity on social media is a wonderful phenomena if it is compared to their writing activity in the classroom. This qualitative descriptive research used questionnaire as the instrument in collecting the data, which are then analyzed by applying theory of emotion, motivation, and computerized learning media. This research concluded that communicator authenticity is not the only trigger of students’ motivation to write on social medium, but the value and the meaning given by the students toward the social media itself that play an important role. Features, easiness, and emotional fulfillment to write are the other triggers which motivate students to write frequently on the social media. The academic significance of this research shows an opportunity for the lecturer to increase students writing motivation in the classroom-based writing activity or in the other academic contexts.